DEVELOPMENT AND EVALUATION OF CONTROLLED RELEASE FORMULATION OF LAMIVUDINE BASED ON MICROPOROUS OSMOTIC TABLET TECHNOLOGY USING FRUCTOSE AS OSMOGEN - Chinmaya Keshari Sahoo; Surepalli Ram Mohan Rao; Muvvala Sudhakar (Indonesian Journal of Pharmacy, 2017)
The present study was undertaken to develop controlled release osmotic pump tablets of lamivudine a nucleoside reverse transcriptase inhibitor for the treatment of acquired immune deficiency syndrome (AIDS).The tablets were prepared by wet granulation method using controlled release polymer hydroxyl propyl methyl cellulose (HPMCE5 LV), MCC as diluent, starch as binder and fructose as osmogen. The coating solution of core tablets were prepared by using cellulose acetate,poly ethylene glycol 400,600,4000,6000 and acetone to quantity sufficient with sorbitol for different batches. The prepared tablets were evaluated for pre compression parameters, post compression parameters, in vitro drug release study and scanning electron microscopy study. Among the prepared formulations LF4 batch show 97.78% drug release in 12hrs.The in vitro release kinetics were analyzed for different batches by different pharmacokinetic models such as zero order, first order,Higuchi,Korsmeyer Peppas and Hixon Crowell model. Short term stability study at 40±2ºC/75±5% RH for three months on the best formulation was performed showing no significant changes in thickness, hardness, friability, drug content and in vitro drug release.